(untitled) (Research, Society and Development, 2020)
It is known that textbooks (LD) are full of images and that they play an important role in student learning. Therefore, we sought to verify how the images are being worked within the content of Colligative Properties in three books adopted by the National Textbook Program for High School (PNLEM) in 2015. The research was developed through an approach qualitative documentary type, in addition to having been based on the parameters of Perales and Jiménez (2002), through analysis instruments such as functionality, relationship with the text and verbal labels. The results showed that the three books surveyed were well matched to the parameters and that their images were not far from the content. With this, we believe that the teacher can choose to use the three books, thus having a more dynamic and concise class with the use of images.